2020
DOI: 10.1186/s12967-020-02539-x
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota from coronary artery disease patients contributes to vascular dysfunction in mice by regulating bile acid metabolism and immune activation

Abstract: Background The gut microbiota was shown to play a crucial role in the development of vascular dysfunction, and the bacterial composition differed between healthy controls and coronary artery disease patients. The goal of this study was to investigate how the gut microbiota affects host metabolic homeostasis at the organism scale. Methods We colonized germ-free C57BL/6 J mice with faeces from healthy control donors (Con) and coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…The abundance of Eggerthella is increased in patients with Rett syndrome, and it induces alterations in short-chain fatty acids profiles ( 29 ). Colonization of Eggerthella in patients with coronary artery disease resulted in increased circulating cholesterol levels ( 30 ). The alteration of lipid metabolites in POI with respect to Eggerthella is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of Eggerthella is increased in patients with Rett syndrome, and it induces alterations in short-chain fatty acids profiles ( 29 ). Colonization of Eggerthella in patients with coronary artery disease resulted in increased circulating cholesterol levels ( 30 ). The alteration of lipid metabolites in POI with respect to Eggerthella is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic pathway analysis found multiple disease-associated metabolic pathways; for instance, it was shown that "Bile Acid Biosynthesis" was related to CAD, which was consistent with the prior finding. Recent evidence suggested that inhibition of liver bile acid synthesis can lead to elevated serum cholesterol levels in a highfat diet, which in turn affected the development of CAD (Liu et al, 2020). Meanwhile, in observational studies, the serum total bile acids of CAD patients were lower than those of non-CAD patients, and the lower concentration of total bile acids was independently and significantly correlated with the presence and severity of CAD (Li et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of primary/secondary BAs depends on the situation. For healthy people, the ratio in the duodenal fluid is about 5 to 6 [109,110], the ratio in feces is around 4, with primary BAs accounting for 80% [111] and the ratio of DCA metabolites to CA metabolites in serum is close to 5 [112]. However, for patients with colorectal cancer or polyps, the proportion of secondary BAs significantly increased [113], especially the LCA.…”
Section: Bile Acid Metabolismmentioning
confidence: 99%